Dynamic response of a SWATH vessel for installing pre-assembled floating wind turbines. (March 2023) - Liu, Ting; Halse, Karl H.; Leira, Bernt J.; Jiang, Zhiyu; Chai, Wei; Brathaug, Hans-P.; Hildre, Hans P.
Abstract: New and efficient installation concepts which can reduce the cost of developing an offshore wind farm are of particular interest. This paper explores a promising concept using the small water-plane area twin-hull vessel (SWATH) to install pre-assembled wind turbines (OWT) onto floating spar foundations. A focus is placed on the hydrodynamic performance of the SWATH and the response analysis of the coupled SWATH-spar system. Firstly, the numerically calculated difference-frequency wave force effect and damping forces of the original SWATH were verified with experimental data. Secondly, the original SWATH was modified to satisfy the criteria of weight-carrying capacity and hydrostatic stability. Thirdly, a multibody numerical model for the SWATH-spar system was developed, in which the hydrodynamic and mechanical couplings between the SWATH and a spar were considered. The SWATH is equipped with a dynamic positioning system to counteract the slow-drift wave force effects. The nonlinear time-domain simulations were carried out for the mating stage when a wind turbine is lifted above the spar foundation. Based on the analysis of statistics of the relative displacement and velocity of the tower bottom and the spar top, the installation concept with SWATH is found to be of decent performance. Finally, recommendations are provided for future research on this concept, which contributes to developing next-generation installation concepts for bottom-fixed and floating wind farms. Highlights: A novel concept for installing the pre-assembled offshore wind turbine using a SWATH vessel is proposed. The numerical model for estimating the SWATH's hydrodynamic responses is verified using the experimental data. An effective mechanical coupling device between the floating spar and the SWATH is introduced during the mating process. The nonlinear time-domain simulations were carried out for the mating stage when the wind turbine was lifted above the spar. The proposed concept can substantially improve the efficiency of offshore wind turbine installation.